Knowledge transfer from experienced to emerging aquaculture industries in developing countries: the case of shrimp and pangasius in Bangladesh. Issue 2 (3rd April 2021) - Islam, Imranul; Nielsen, Max; Badiuzzaman, Badiuzzaman; Schulze-Ehlers, Birgit
ABSTRACT: The shrimp industry of Bangladesh is well experienced and almost the sole contributor to fish export. The rapid growth of pangasius aquaculture has emerged as a new opportunity for export but the export path is uneven for a new species. This article identifies areas where the pangasius industry can use knowledge obtained from the development of the shrimp industry to develop its own export opportunities. The shrimp industry has developed infrastructure and a specific legal framework in the form of e-traceability and licensing to comply with food safety and certification requirements of its global buyers. The pangasius industry can also learn from the mistakes of the shrimp industry, particularly those concerning planned ponds and dike systems. The experience of the shrimp industry is a new school of learning for the pangasius industry to get access to the global market.